Corporate social responsibility in Islamic banks - Sikorska, Marta (Społeczna odpowiedzialność biznesu w bankach islamskich, 2020)
The main objective of this article is to examine to what extent the banks operating in accordance with Sharia law consider the concept of corporate social responsibility as an overriding priority. As a thesis, the statement has been adopted that the religion of Islam significantly contributes to the application of this concept in Islamic financial institutions. To verify this thesis statement, a literature overview and induction study methods were used. In addition, a study of the information provided by selected banks operating in accordance with Sharia law, with offices in the United Kingdom, Saudi Arabia and Kuwait, was carried out. The examination allows to conclude that Sharia law has a significant impact on the concept of corporate social responsibility in Islamic financial institutions. Islam recognizes this concept as paramount in the functioning of entities. In fact, every institution works to make a profit. In the functioning of Islamic entities, however, it is important that an entity making a profit does not overlook the moral and ethical norms that are characteristic of Islam and, most importantly, does not neglect fair tax calculation
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 12, s. 113-123